West Bank and Gaza Energy Sector Review - World Bank (Washington, DC, 2014)
This report examines the energy sector in the West Bank and Gaza. It finds that from the perspective of its energy sector, West Bank and Gaza is in an unusual position in at least three respects: 1) Because of political and logistical factors, nearly all of these supplies at present come from Israel; 2) A second unusual challenge faced by West Bank and Gaza is its fragmentation into two distinct geographical zones with divergent economic characteristics and 3) A third unusual challenge is the constraints imposed by Israeli policies and actions on the ability of the Palestinian Authority (PA) to operate and develop its energy systems. This Review addresses the question of how the energy sector can make an effective contribution to the economic recovery and long-term growth of West Bank and Gaza in this situation. It does so by examining the broad regional and strategic dimensions relating to the sector that form the basis of a sustainable investment and institutional development program. This Review is structured in three parts. The first part is this Executive Summary that presents the recommendations of the Review, which are grouped at the end of this summary. They are based on analysis developed in the main chapters of the Review that comprise the second part. These chapters deal with specific aspects of the energy sector, namely the current pattern of energy supply and consumption, the technical and financial performance of the power utilities, the impact of the energy sector on the PA's recurrent budget, the natural gas market, and the investment requirements in the electricity system and associated fuel supply facilities for West Bank and Gaza. These chapters in turn are supported in the third part of the Review by technical annexes that examine in some detail specific aspects such as oil products supply and demand, the demand for electricity, and power network investment needs in West Bank and Gaza, the performance of the Gaza Power Plant (GPP), and developments in the Israeli natural gas and electricity markets that have a bearing on the energy sector in West Bank and Gaza.